Ba–Cu ordering in bariopharmacoalumite-Q2a2b2c from Cap Garonne, France. (August 2014) - Grey, I. E.; Mumme, W. G.; Price, J. R.; Mills, S. J.; Macrae, C. M.; Favreau, G.
Abstract: Bariopharmacoalumite- Q 2 a 2 b 2 c, Ba0.5 (Cu, ZnO)0.1 H0.6 [Al4 (OH)4 (As0.9 Al0.1 O4 )3 ]·5.5H2 O, from the south mine of the old copper mine at Cap Garonne, France, has a 2 × 2 × 2 I -centred tetragonal superstructure of the basic pharmacosiderite-type structure. Cell parameters are a = 15.405(2) Å and c = 15.553(3) Å. The structure was determined and refined in I 2 m to R 1 = 0.057 for 2697 reflections with I > 2σ( I ), using synchrotron X-ray data on a twinned crystal. The origin of the superlattice cell doubling was determined to be due predominantly to the ordering of Ba atoms in half of the [0 0 1] channels, centred at (0, 0, 0) and (½, ½, 0). The other channels, centred at (½, 0, 0) and (0, ½, 0), were found to be occupied by corner-connected chains of Cu/Zn-centred square planar units.